Neonatal seizures: the Dublin Collaborative Study. Issue 9 (September 1988) - Curtis, P D; Matthews, T G; Clarke, T A; Darling, M; Crowley, P; Griffin, E; O'Connell, P; Gorman, W; O'Brien, N; O'Herlihy, C
Abstract : Asphyxial seizures occurred in 89 of 101, 829 infants born alive at term (0.87/1000) in three large maternity hospitals from January 1980 to December 1984. These seizures were significantly associated with antenatal complications, primiparity, and prolonged pregnancy. Meconium staining of the amniotic fluid was also associated with asphyxial seizures, but there were high false positive (11%) and false negative (50%) rates. Fifteen of the infants who had seizures died (18%) and 21 (25%) were handicapped at 1 year. Outcome was most successfully predicted by the way the infant was feeding at 1-2 weeks. All infants taking more than half their estimated requirements by mouth at 1 week were normal, and those still being fed by tube at 2 weeks were handicapped.